Comparative techniques for detecting mastitis disease in bovine milk samples - Gupta, Amit; CHOPADE, DEVDAN; B JADHAV, JAYDEEP; TAMBOLI, SALIM; SHINDE, BHARAT (Innovare Journal of Medical Sciences, 2017)
Objective-The objective of our study is to analyze various techniques that are applied for detecting mastitis disease in milk samples. Methods- In this study, we collect milk samples (n=100) from different dairy farms and diagnosed through various tests. In addition, flow cytometric analysis was also performed for milk samples in order to analyzed lymphocytes, monocytes and granulocytes count. Results- The results of these studies showed that California mastitis Test (CMT) showed much more positive results against mastitis disease as compared to other techniques whereas flow cytometric results revealed that during mastitis disease, there is enhancement in granulocytes count. Conclusion- Out of these techniques, CMT is the most reliable and cost effective method for detecting mastitis disease.